Trends in Socioeconomic Inequalities in the Use of Antenatal Care Services by Women Aged 15 to 49 Years in Vietnam. (July 2019) - Kien, Vu Duy; Jat, Tej Ram; Phu, Tran Van; Cuong, Le Manh; Anh, Vu Thi Mai; Chu, Nguyen Van; Duong, Tran Trong; Long, Vo Hoang; Dung, Tham Chi
Despite considerable variations in the use of antenatal care (ANC) services in Vietnam, limited information is available on socioeconomic inequalities concerning the use of ANC services. This study aimed to assess the trends and changes in socioeconomic inequalities in the use of ANC services by women aged 15 to 49 years in Vietnam from 2006 to 2014. We used data from the Multiple Indicator Cluster Survey conducted in 2006, 2011, and 2014. The percentage of women who received ANC services increased significantly from 26.5% in 2006 to 42.7% in 2011 and reached 56.6% in 2014. We found a decreasing trend in the concentration indices of the use of ANC services from 0.36 in 2006 to 0.19 in 2014. The common factors significantly associated with the higher percentage of the use of ANC services in 2006, 2011, and 2014 were women belonging to the Kinh and Hoa ethnic groups and belonging to wealthier groups. Our study showed a reduction in socioeconomic inequality in the use of ANC services between 2004 and 2014. However, significant inequalities still exist in the use of ANC services based on women's education, ethnicity, and economic status.